The Effectiveness of Total Physical Response (TPR) Using Stortytelling In Teaching English Vocabulary At SDN 017 Marangkayu - Aidil Satriani; Rostanti Toba; Anis Komariah (PT. Berkah Smart Academica, 2024)
Vocabulary is one of the aspects of language that has to be learned because it is important for daily activities and the classroom teaching and learning process, particularly in English classes. Despite this, many students may still struggle to learn a new word in English. The teacher must be more creative and innovative in implementing methods to make students feel comfortable learning English because there are many factors that must be achieved and it requires more concentration to master it. The approach employed in this research was quantitative, using a quasi-experimental design to compare two classes. The fourth graders in SDN 017 Marangkayu served as the samples. Class IV (A) and IV (B) were the samples of this research, with 14 students in the experimental class and 14 in the control class. Multiple-choice examinations served as the research instrument. The researcher utilized the SPSS version 21 program and the independent sample t-test formula to evaluate the data. This research used observation and documentation data collection techniques that have been tested for validity and reliability, and the data has met the requirements for normality and homogeneity. The researcher concluded that Total Physical Response (TPR) using storytelling was effective to improve student’s achievement in learning new vocabulary. The result of the data was obtained by giving pre-test and post-test to both groups, and the 2-tailed significance value was obtained at 0,08 < 0,05, which means that H0 is rejected and Ha is accepted. So, this research shows that TPR using storytelling has a significant effect on teaching vocabulary to students.